2020
DOI: 10.1021/acsaem.0c02187
|View full text |Cite
|
Sign up to set email alerts
|

ReS2: A High-Rate Pseudocapacitive Energy Storage Material

Abstract: Transition-metal dichalcogenides have attracted exceptional attention in the field of energy storage such as lithium-ion batteries and supercapacitors because of their unique electronic, optical, and mechanical properties. In this work, we synthesized rhenium disulfide (ReS 2 ) on high-throughput, electronics industry-standard, screen-printed electrodes (SPEs) to use as an electrode material for supercapacitor application. The ReS 2 nanoparticles were grown by a room-temperature, aqueoussolution-based electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…As shown in Figure b, the high-resolution XPS core spectrum of Mo 3d fits into five peaks at 226.21, 228.8, 232.02, 229.35, and 232.73 eV corresponding to S 2s, 2H Mo 3d 5/2 , 2H Mo 3d 3/2 , 1T Mo 3d 5/2 , and 1T Mo 3d 3/2 , respectively. The HR-XPS Re 4f spectrum shows two peaks at 41.59 and 43.96 eV assigned to 4f 7/2 and 4f 5/2 , respectively (Figure c) . In addition, the deconvolution of the S 2p spectrum shows four peaks (Figure d).…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure b, the high-resolution XPS core spectrum of Mo 3d fits into five peaks at 226.21, 228.8, 232.02, 229.35, and 232.73 eV corresponding to S 2s, 2H Mo 3d 5/2 , 2H Mo 3d 3/2 , 1T Mo 3d 5/2 , and 1T Mo 3d 3/2 , respectively. The HR-XPS Re 4f spectrum shows two peaks at 41.59 and 43.96 eV assigned to 4f 7/2 and 4f 5/2 , respectively (Figure c) . In addition, the deconvolution of the S 2p spectrum shows four peaks (Figure d).…”
Section: Results and Discussionmentioning
confidence: 93%
“…In the family of transition metal dichalcogenides (TMDs), besides MoS 2 , ReS 2 has received much more attention in energy storage devices due to its weak interlayer interaction and a large interlayer spacing of 0.614 nm. Recently, Ghosh et al 21 fabricated ReS 2 on screen-printed electrodes with an area capacitance of 156 mF cm −2 at 1.6 mA cm −2 . Veerakumar et al 22 prepared rhenium nanoparticledecorated activated carbon, which delivers a specific capacitance of 181 F g −1 with 90% of capacitance retention over 2500 cycles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electrolytic electron donor ions are adsorbed across the electrode surface in case of redox mechanism whereas channeled through the electrode layered surface in case of intercalation/decalation mechanism Figure 3(b) (Augustyn et al, 2014). Transition metal sulfides, metal oxides, metal carbides, metal nitrides, as well as conducting polymers are typically considered pseudocapacitive materials due to their high ionic conductivity to induce pseudocapacitance (Ghosh et al, 2020;Muniraj et al, 2020;Yuan et al, 2020;Zhang, Cockreham, et al, 2020). The pseudocapacitive storage F I G U R E 3 Working principle of (a) electric double layer capacitors and (b) pseudocapacitors mechanism is often confused with battery type non-capacitive storage mechanisms where bulk intercalation type redox faradic charge transfer is obeyed.…”
Section: Capacitive and Non-capacitive Energy Storagementioning
confidence: 99%
“… 40,41 In fact, it has been reported that the photoluminescence (PL) intensity in ReS 2 increases with an increase in the number of layers, making it a transcendent candidate for the aforementioned application. 40 Although the supercapacitor performance of ReS 2 has been studied recently, along with the solar driven charge storage properties, 42,43 the light effect on the charge storage properties of direct band gap materials (such as ReS 2 multi-layers grown on a conducting substrate) remains unexplored.…”
Section: Introductionmentioning
confidence: 99%